Yaiba, samurai legend. 2 - Aoyama, Gōshō (Shōnen Sandē komikkusu., 2025)
Yaiba Kurogane is an energetic young swordsman who's grown up in the jungle, training to be a samurai with his father, Kenjuro. When they return to Japan, chaos seems to follow wherever Yaiba goes! Destined to be a legendary hero, Yaiba must learn to be a true samurai and save the world! Yaiba, accompanied by the 400-year-old Musashi Miyamoto, and his friends Sayaka, Kagetora, and Shonosuke, embarks on a training journey so he can defeat Onimaru. Onimaru, now a demon, has seized control of Japan and turned the parliament building into Onimaru Castle! His sights are set on Raijinken-Yaiba's Thunder God Sword-and he'll stop at nothing to take it!